Polyaniline-modified cellulose nanofibrils as reinforcement of a smart polyurethane - Auad, María L. (2011)
Segmented polyurethanes exhibiting shape memory properties were modified by the addition of polyaniline (PANI)-coated cellulose nanofibrils (CNFs). The two-phase structure of the polymer is responsible for the material's ability to ‘remember’ and autonomously recover its original shape after being deformed in response to an external thermal stimulus. PANI was grown on the surface of the CNFs via in situ polymerization. Modified nanocrystals were added to the segmented polyurethane in concentrations ranging from 0 to 15 wt%. The changes in the material properties associated with the percolation of the coated fibrils appear at higher concentrations than previously observed for non-modified CNFs, which suggests that fibril agglomeration is occurring due to the PANI coating. The shape memory behavior of the composites is maintained at about the same level as that of the unfilled polyurethane only up to 4 wt% of fibrils. At higher concentrations, the rigidity of the nanofibrils as well as their interaction with the hard-segment phase and the increasing difficulty of dispersing them in the polymer collaborate to produce early breakage of the specimens when stretched at temperatures above the melting point of the soft segments.